2022
DOI: 10.1038/s41467-022-28855-y
|View full text |Cite
|
Sign up to set email alerts
|

The control of transcriptional memory by stable mitotic bookmarking

Abstract: To maintain cellular identities during development, gene expression profiles must be faithfully propagated through cell generations. The reestablishment of gene expression patterns upon mitotic exit is mediated, in part, by transcription factors (TF) mitotic bookmarking. However, the mechanisms and functions of TF mitotic bookmarking during early embryogenesis remain poorly understood. In this study, taking advantage of the naturally synchronized mitoses of Drosophila early embryos, we provide evidence that GA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…One explanation for the difference may be the residence time on DNA. While Zelda binds DNA only transiently on the order of seconds 46 , GAF multimerizes on DNA and remains on chromatin on the order of minutes [119][120][121][122] . Such stable binding makes sense in the light of GAF's role in 3D genome structure [122][123][124][125][126] and transcriptional memory 120,127,128 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for the difference may be the residence time on DNA. While Zelda binds DNA only transiently on the order of seconds 46 , GAF multimerizes on DNA and remains on chromatin on the order of minutes [119][120][121][122] . Such stable binding makes sense in the light of GAF's role in 3D genome structure [122][123][124][125][126] and transcriptional memory 120,127,128 .…”
Section: Discussionmentioning
confidence: 99%
“…While Zelda binds DNA only transiently on the order of seconds 46 , GAF multimerizes on DNA and remains on chromatin on the order of minutes [119][120][121][122] . Such stable binding makes sense in the light of GAF's role in 3D genome structure [122][123][124][125][126] and transcriptional memory 120,127,128 . Thus, GAF could generate accessible chromatin but by binding to the newly opened DNA itself, it could partially occlude the binding of additional TFs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the multimerization of proteins via the BTB domain can increase the binding affinity for several motifs located in close vicinity. Such a mechanism was previously demonstrated for the pioneer and bookmarking protein GAF that is stably associated with chromatin [45, 63]. GAF has only one zinc finger domain that binds to a GAGAG motif.…”
Section: Discussionmentioning
confidence: 87%
“…Several have been implicated in chromatin architectural function, acting as a component of a chromatin insulator complex (Mod(mdg4)) or recruiting chromatin remodeling complexes (GAF, Pipsqueak) [14,43,44]. Recently, it was shown that GAF is a pioneer factor that acts as a stable mitotic bookmarker during zygotic genome activation during Drosophila embryogenesis [45,46]. TTK-type BTB domains contain a highly conserved N-terminal FxLRWN motif, where x is a hydrophilic residue [31].…”
Section: Introductionmentioning
confidence: 99%
“…Live imaging of Zld protein shows that the factor releases from chromatin as mitosis initiates 40 , and the chromatin accessibility of Zld-bound sites is reduced as nuclei divide 28 . In contrast, GAF binds both interphase and mitotic chromatin, and mitotic GAF-bound sites remain accessible 41 . This difference appears to result from the longer residence time of GAF on chromatin that allows persistent binding to mitotic chromosomes.…”
Section: Pioneer Factors… How Do They Work?mentioning
confidence: 98%